Pengaruh Komunikasi Interpersonal dan Disiplin Belajar Terhadap Hasil Belajar Siswa Sekolah Minggu Buddha di Jawa Barat - Alexander Candra; Isomudin Isomudin; Ida Bagus Dharmika; Yanah Sucintani; Oey Hannes Widjaya (Dhammavicaya : Jurnal Pengkajian Dhamma, 2023)
Thepurpose of the research testinghowmuch influence the interpersonal communicationon the learning outcomes of Buddhist Sunday School students in West Java.Test how much the influence of learning discipline on the learning out comes of Buddhist Sunday School students in West Java. Test how much influence the interpersonal communication and learning discipline together on the learning out comes of Buddhist Sunday School students in West Java.